Overweight worsens the metabolic presentation of type 1 diabetes mellitus in children - Muzslay, Eszter; Herczeg, Vivien; Pusztai, Rozália Ildikó; Forstreuter, Vilmos Zoltán; Soós, Dorina; Takács, Johanna; Tóth-Heyn, Péter; Luczay, Andrea (Frontiers in Endocrinology, 2026)
IntroductionThe prevalence of both obesity and type 1 diabetes mellitus (T1DM) has increased globally over the last decades. Overweight and obesity affect individuals with T1DM and influence not only the autoimmune pathogenesis but also the long-term complications of T1DM. This study aimed to investigate the effect of excess body weight on the clinical presentation of T1DM.MethodsWe conducted a retrospective, single-center cohort study at the largest pediatric endocrinology center in Hungary. Data were collected from children diagnosed with T1DM between 2014 and 2023. A total of 994 patients’ presentation parameters and anthropometric data were analyzed. Based on BMI Z-scores, patients were categorized into three groups (normal-weight, overweight, and obese). Metabolic parameters at diagnosis were compared between groups.ResultsThe combined ten-year prevalence of overweight and obesity was found to be 15.9%. Significant between-group differences were observed in pH (p=0.005), bicarbonate (HCO3-; p=0.018), partial carbon-dioxide (pCO2) pressure (p=0.018), and C-peptide levels (p< 0.001). Lower pH, pCO2 and HCO3- levels were found among those who were overweight, and higher C-peptide levels in children with obesity. Diabetic ketoacidosis (DKA) and severe DKA were seen at a significantly higher rate among children with overweight and obesity (p=0.013; p< 0.001).DiscussionChildren with overweight presented with more severe metabolic derangement at T1DM onset. Obese and overweight children have a higher risk of having DKA at presentation despite elevated C-peptide levels, which suggest a greater residual β-cell function. These findings support the hypothesis that other factors, such as chronic inflammation, may contribute to T1DM manifestation. Our findings highlight the impact of overweight and obesity on the clinical presentation of T1DM. In case of weight loss in obese and overweight children, more attention should be paid to the classical symptoms of T1DM.